Pteridophyta Diversity and Sorus Variation in The Pasmah Riverbank Central Bengkulu - Angelina br Sebayang; Bhakti Karyadi; Mellyta Uliyandari; Deni Parlindungan; Nirwana Nirwana; Rendi Zulni Ekaputri (BIOEDUKASI, 2023)
Pteridophyta plants as plant communities in biodiversity have important ecological functions in rivers and human life. One of the habitats for ferns in the upper reaches of the river in Bengkulu is the Pasmah River. The Pasmah River is a source of water for the people of Bengkulu and its surroundings. To maximize the role of the river, it is necessary to make an inventory of plants around the river, one of which is ferns. This study aims to determine the diversity of types and variations of pteridophyta sorus. A sampling of ferns was carried out on the banks of the Pasmah River, Central Bengkulu. Purposive sampling was used in this study to pinpoint the location, and the cruising (cruise method) was used to collect sample data. The results showed that there were 15 types of ferns where 12 types of ferns were found with sorus, 6 types of ferns were round, 4 were elongated, 1 was in line, 1 was strobili and 3 species had no sorus.